2008
DOI: 10.1007/s10834-008-9105-z
|View full text |Cite
|
Sign up to set email alerts
|

Saving for Children’s College Education: An Empirical Analysis of the Trade-off Between the Quality and Quantity of Children

Abstract: Children, College expenses, Life-cycle theory of saving and consumption, Quality–quantity model of fertility,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The odds of saving for children's education was found to be higher for those with fewer children (Yilmazer 2008), those with a higher education, and those who were Asian or Hispanic (Lee et al 1997). The findings of Xiao and Fan (2002) indicated that American households were more likely than Chinese households to report major purchases as a saving motive when household size increased.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The odds of saving for children's education was found to be higher for those with fewer children (Yilmazer 2008), those with a higher education, and those who were Asian or Hispanic (Lee et al 1997). The findings of Xiao and Fan (2002) indicated that American households were more likely than Chinese households to report major purchases as a saving motive when household size increased.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…Previous research that examined saving motives of Chinese households reported the main effects of demographic and economic characteristics on saving motives (e.g., DeVaney et al 2007;Xiao and Fan 2002;Xiao and Noring 1994;Yilmazer 2008). …”
Section: Contributions Of This Studymentioning
confidence: 99%
“…Larger sibships are associated with a lower probability of attending college (Conley 2001), lower parental investments (Powell and Steelman 1989; Steelman and Powell 1989; Yilmazer 2008) in any one child, and lower saving (Steelman and Powell 1991) for each child’s education. Powell and Steelman (1989) measure sibship size separately by gender and find that an additional brother reduces parental financial support for a college education more than an additional sister.…”
Section: 0 Introductionmentioning
confidence: 99%
“…Using data from the 1983–1986 SCF, Yilmazer (2008) studied the effect of children’s college expenses on household savings. Cross‐tabulation was conducted to study the relationship between household saving motives and the number of children.…”
Section: Literature Reviewmentioning
confidence: 99%